Memories of Academician Professor Vyacheslav Vsevolodovich Ivanov, on the Occasion of the Fifth Anniversary of His Death - Eckert, Rainer (Slavistica Vilnensis, 2023)
Born on August 21, 1929 in Moscow, Vjačeslav Vsevolodovič Ivanov died on October 7, 2017 in Los Angeles. The beginning of an unprecedented scientific career of Vjačeslav Vsevolodovič was interrupted by a ruthless political campaign of the MGU management in 1959, which ended with Vjačeslav Vsevolodovič’s expulsion from the university. Those in power at the time condemned Vjačeslav Vsevolodovič Ivanov for his public ne gation of the official verdict on the novel by B.L. Pasternak doctor Živago and in support of the scientific views of the world-renowned linguist prof. dr. Roman Osipovic Jacobson. The life and work of VJAČESLAV VSEVOLODOVIČ IVANOV, based on the many languages and the literatures that existed through them, which he researched and communicated to people (and especially to student youth) in a rarely encountered way, were through a constant intrusion in science about man and in art and closely linked with a deep humanism and an exemplary empathy. From the Editor. The memoirs of the famous German baltist Rainer Eckert about Vyacheslav Vsevolodovich Ivanov, member of the Russian Academy of Sciences, director of the Institute of World Culture at Moscow State University and professor in the Department of Slavic and East European Languages and Literatures at the University of California, an outstanding scholar of encyclopedic outlook, are dedicated to the fifth anniversary of his death. The Memoirs of Prof. Rainer Eckert are published without changes, with the author’s references to the books and articles mentioned in the text.